Treatment of atrial fibrillation with radiofrequency ablation and simultaneous multipolar mapping of the pulmonary veins - Rocha Neto,Almino C. (2001)
OBJECTIVE: To demonstrate the feasibility and safety of simultaneous catheterization and mapping of the 4 pulmonary veins for ablation of atrial fibrillation. METHODS: Ten patients, 8 with paroxysmal atrial fibrillation and 2 with persistent atrial fibrillation, refractory to at least 2 antiarrhythmic drugs and without structural cardiopathy, were consecutively studied. Through the transseptal insertion of 2 long sheaths, 4 pulmonary veins were simultaneously catheterized with octapolar microcatheters. After identification of arrhythmogenic foci radiofrequency was applied under angiographic or ultrasonographic control. RESULTS: During 17 procedures, 40 pulmonary veins were mapped, 16 of which had local ectopic activity, related or not with the triggering of atrial fibrillation paroxysms. At the end of each procedure, suppression of arrhythmias was obtained in 8 patients, and elimination of pulmonary vein potentials was accomplished in 4. During the clinical follow-up of 9.6±3 months, 7 patients remained in sinus rhythm, 5 of whom were using antiarrhythmic drugs that had previously been ineffective. None of the patients had pulmonary hypertension or evidence of stenosis in the pulmonary veins. CONCLUSION: Selective and simultaneous catheterization of the 4 pulmonary veins with microcatheters for simultaneous recording of their electrical activity is a feasible and safe procedure that may help ablation of atrial fibrillation.